Implementasi Evaluasi Berbasis Hots ( Higher Order Thinking Skill) Terhadap Peningkatan Kemampuan Penalaran Verbal Siswa Dalam Pembelajaran Pai Di Smpn 7 Bekasi - Eva Dwi Kumala Sari (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
Increasing the ability to think at a high level in schools is an important foundation to help students in reasoning and understanding Islamic religious education in depth. One of the things that can be done by schools to improve higher order thinking skills and reasoning is to provide continuous evaluation of HOTS-based learning, which is the object of this research is to find out: (1) whether there is an influence between the implementation of HOTS-based evaluation of improvement verbal reasoning ability of students in learning PAI.This research was conducted at SMPN 7 Bekasi. The sample in this study were 70 students using cluster random sampling. Data in this study were analyzed using regression analysis, with a significance level of Î± = 0.05. The results of this study are: (1) There is an effect between the implementation of the HOTS-based evaluation of improving students' verbal reasoning skills in PAI learning. Keywords: HOTS-based evaluation, verbal reasoning.